Analysis for quality of senggugu plant and herbal product (Rotheca Serrata (L.) with metabolomics approach - Qodriah, Rahmatul; Aziz, Zuhelmi; Damayanti, Volin; Alya, Aura Dyah (Faculty of Pharmacy, Universitas Pancasila, 2024)
Senggugu plant (Rotheca serrata (L.) has many benefits and has the potential as a raw material for herbal medicine, so an identify in the form of an FTIR fingerprint profile is needed. The purpose of this study was to ensure the quality of simplisia and herbal product of senggugu roots and leaves by metabolomics approach. Simplisia and herbal products powder of senggugu leaves and roots were extracted with 70% ethanol solvent using ultrasonic method. The dried extracts of simplisia and herbal products were analyzed by FTIR and TLC-Densitometry. Data obtained from FTIR and TLC-Densitometry analyzed with multivariate data analysis techniques, Principal Component Analysis (PCA) to obtain fingerprint profiles. The PCA results obtained a total Principal Component value of 98,7% and showed that leaf simplisia and herbal products of senggugu leaves can cluster well, while root simplisia and herbal products of senggugu roots were at a distance from the plot. The analysis with OPLS-DA showed the same fungtional groups, which are C=H, O-H, C=C. The results of antioxidant activity testing of 70% ethanol extracts of leaves, roots, and herbal products of senggugu obtained strong antioxidant activity ability with IC50 values of 80,08; 92,12; 80,53; and 94,03 ppm.